2014
DOI: 10.1111/jeb.12491
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary neutrality of mtDNA introgression: evidence from complete mitogenome analysis in roe deer

Abstract: Introgressive hybridization offers a unique platform for studying the molecular basis of natural selection acting on mitogenomes. Most of the mtDNA protein-coding genes are extremely conserved; however, some of the observed variations have potentially adaptive significance. Here, we evaluated whether the evolution of mtDNA in closely related roe deer species affected by widespread mtDNA introgression is neutral or adaptive. We characterized and compared 16 complete mitogenomes of European (Capreolus capreolus)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 57 publications
4
18
0
Order By: Relevance
“…Mitochondrial genome introgression in particular is commonplace among animals, and sequence variation in mtDNA has largely been treated as neutral in the evolutionary literature (Ballard & Kreitman ; Matosiuk et al . ). However, mitochondrial genetic variation can be critically important to the fitness of individuals (Dowling et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Mitochondrial genome introgression in particular is commonplace among animals, and sequence variation in mtDNA has largely been treated as neutral in the evolutionary literature (Ballard & Kreitman ; Matosiuk et al . ). However, mitochondrial genetic variation can be critically important to the fitness of individuals (Dowling et al .…”
Section: Introductionmentioning
confidence: 97%
“…While considerable evolutionary theory is focused on change within or the splitting of genetic lineages, introgression of genes across species boundaries is also an important evolutionary process (Arnold 1992;Rhymer & Simberloff 1996;Mallet 2005;Schwenk et al 2008). Mitochondrial genome introgression in particular is commonplace among animals, and sequence variation in mtDNA has largely been treated as neutral in the evolutionary literature (Ballard & Kreitman 1995;Matosiuk et al 2014). However, mitochondrial genetic variation can be critically important to the fitness of individuals (Dowling et al 2008), cause numerous diseases (Wallace 1999) and lead to differences in energy generation among species (Castoe et al 2008;Shen et al 2010;Pichaud et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of the ''DHU'' arm in tRNA Ser has been reported in other species of Cervidae [8,21,[25][26][27]35]. The non-coding control region contains conserved sequence blocks, and termination-associated sequences; and can be used for fine-scale population studies, since it is amongst the most rapidly evolving segments in the animal mtDNA [17,19,24,28]. The high-throughput approach for sequencing was useful for obtaining the whole mitochondrial genome of red deer, so this method could be used broadly among animal taxa.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, the sequences described may have been misidentified. For example in the case of Capreolus species, from which some are described as belonging to Capreolus pygargus [17], but deposited in GenBank as Capreolus capreolus. A second example of possible species assignation error concerns Mazama rufina and Pudu mephistophiles, which share very similar mtDNA genomes (98.6%).…”
Section: Acta Biologica Hungarica 67 2016mentioning
confidence: 99%
“…Since then, introgressive hybridization has been widely detected in amphibians, birds, and mammals (e.g., Dowling et al., 2016; Matosiuk, Sheremetyeva, Sheremetyev, Saveljev, & Borkowska, 2014; Mccracken, Wilson, & Martin, 2013; Sequeira et al., 2011; Marshall et al, 2011). In the initial study of introgressive hybridization, Mecham (1960) used the morphological analysis of the green tree frog Hyla cinerea and the barking tree frog Hyla gratiosa ; the research has revealed the strong signal of introgressive hybridization between the two species.…”
Section: Introductionmentioning
confidence: 99%